Associations of long-chain ω-3 fatty acids and fish intake with endometrial cancer risk in the VITamins And Lifestyle cohort. Issue 3 (5th February 2014) - Brasky, Theodore M; Neuhouser, Marian L; Cohn, David E; White, Emily
ABSTRACT: Background: Inflammation plays an important role in endometrial cancer etiology. Long-chain ω-3 (n−3) polyunsaturated fatty acids (PUFAs), derived from marine sources, are thought to be antiinflammatory; however, several studies of fish consumption suggest an increase in risk. Objective: This study examined whether intakes of long-chain ω-3 PUFAs, including eicosapentaenoic acid (EPA; 20:5ω-3) and docosahexaenoic acid (DHA; 22:6ω-3), from diet and supplements and intake of fish are associated with endometrial cancer risk. Design: Between 2000 and 2002, 22, 494 women aged 50–76 y, living in western Washington State, were recruited to the VITamins And Lifestyle cohort study. Incident endometrial cancers ( n = 263) were identified through the Surveillance, Epidemiology, and End Results cancer registry after 9 y of follow-up. Multivariable-adjusted HRs and 95% CIs for the association of intakes of individual long-chain ω-3 PUFAs and fish with endometrial cancer risk were estimated by using Cox proportional hazards. Results: Women in the highest compared with the lowest quintile of dietary EPA + DHA intake had a 79% increased risk of endometrial cancer (95% CI: 16%, 175%; P -trend = 0.026). Results were similar for EPA and DHA measured individually and for fish intake. When data were stratified by body mass index (in kg/m 2 ; <25 or ≥25), increases in risk of long-chain ω-3 PUFAs were restricted to overweight and obese women, and statistically significant reductions in risk were observed for normal-weight women. Conclusions: The overall increased risk reported here confirms the findings of several prior observational studies of fish intake, which observed similar increases in risk. Randomized trials are needed to confirm these findings.